Lactate dehydrogenase is an indicator for outcomes of short-term and long-term in septic patients - Zhao Zeng; Cuirong Guo; Fengning Tang; Ning Ding (PLoS ONE, 2025)
Objective The association between lactate dehydrogenase (LDH) and clinical outcomes in sepsis was explored based on MIMIC-IV database. Methods This was a retrospective study. Models including unadjusted model and adjusted models were performed for exploring the association of LDH with 30-day mortality and 1-year mortality. The smooth fitting curves were constructed by using generalized additive model. The predictive value of LDH for clinical outcomes in sepsis was evaluated. The statistical software of EmpowerStats ( http://www . empowerstats. com) and R ( http://www.R-project.org ) were applied for analysis. Results 6775 sepsis patients were included. After adjusted for all potential confounders, for every 100 IU/L increment in LDH, the risk of 30-day mortality and 1-year mortality increased by 11% (odds ratio (OR)=1.11, 95%CI:1.08–1.13, P < 0.0001) and 12% (OR=1.12, 95%CI:1.09–1.14, P < 0.0001), respectively. The areas under the ROC curve of LDH for predicting mortalities of 30-day and 1-year were 0.667 (95%CI:0.652–0.681) and 0.646 (95%CI: 0.632–0.660), respectively. Conclusion LDH was positively correlated with 30-day and 1-year mortalities in sepsis and the relationship was nonlinear.